Notes on the musical language of Estércio Marquez Cunha in his brass works (Revista NUPEART, 2025)
This text aims to provide notes on the musical language used by composer Estércio Marquez Cunha in his compositions for brass. For the discussion, aspects of Brazilian music from the 20th century are presented in order to contextualize the composer's work in the Brazilian musical panorama of his time. General characteristics of some works that include brass as solo instruments are described and of this set of compositions, the “choral” work is analyzed in more detail. Therefore, the research is bibliographic in nature with document analysis. From the analyzes and reflections, it was possible to observe that Estécio Marquez Cunha's musical language presents elements both from the tradition of Western music and from today, which allows it to stimulate new perceptions.
Keywords: musical language; compositions for metals; Estércio Marquez Cunha